Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Perusahaan General Contractor Karawang - Febri De Khafilian; Dene Herwanto; Wahyudin Wahyudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
Employee performance is the most important element in a company because the results of employee performance greatly affect the output of the company itself. The purpose of this study is to determine whether there is an effect of work motivation and work environment on employee performance at companies engaged in general contractor in the city of Karawang. The variables used in this study are work motivation (X1), work environment (X2) and employee performance (Y). The analytical instrument used is the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, T test, F test, multiple linear regression analysis, and the coefficient of determination. The results of testing the first hypothesis (H1) work motivation has no significant effect on employee performance. The second hypothesis (H2) that the work environment has a significant effect on employee performance. The third hypothesis (H3) work motivation and work environment have a positive and significant effect simultaneously on employee performance in the company.